ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Rizky Liliyani Pasaribu; Jeni Wardi; Wita Dwika Listihana (Jurnal Kajian Akuntansi dan Auditing, 2024)
This study aims to analyze the factors that affect firm value in companies incorporated in the LQ45 Index in Indonesia in the period 2018-2022. The data comes from companies' annual financial statements in the LQ45 Index. The sampling technique used a purposive sampling method by selecting 20 companies from a total of 45 companies in the LQ45 Index. This study covers 2018 to 2022, and data analysis was performed with panel data regression using Eviews 10 software. The results exhibited that overall, the variables of firm size, profitability, capital structure, dividend policy, and stock price positively and significantly influence firm value. Partially, the firm size variable, profitability, as measured by NPM, and capital structure, as measured by DAR, show a negative and significant influence on firm value. In contrast, ROA measures profitability, DER measures capital structure, and the stock price positively and significantly influences firm value. Dividend policy, although showing a negative influence, has no significant effect on firm value.